Globalization Facts and Figures - Masson, Paul (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2001)
Globalization has become the focus for a wide range of protests against various features of the world economy. This paper aims to give a concise summary of the economic dimensions of globalization, while leaving to one side other aspects-such as cultural, environmental, or political ones-that are beyond the scope of the IMF. Periods of increased globalization have tended to be associated with technological innovations that reduce transportation and communications costs and with generally rising standards of living. Moreover, countries that have embraced openness to the rest of the world have done better than those that have not. Nevertheless, globalization may also be associated with increased inequality and volatility, which may justify strengthening domestic safety nets and financial supervision and regulation, and enhancing international economic policy coordination. The IMF helps to ensure economic gains from globalization by encouraging trade liberalization, reducing countries' vulnerability to crises, lending to them when they are in difficulty, and assisting them in putting in place structural reforms that help reduce poverty.